2009
DOI: 10.1038/nmeth.1356
|View full text |Cite
|
Sign up to set email alerts
|

G-TRACE: rapid Gal4-based cell lineage analysis in Drosophila

Abstract: We combine Gal4/UAS, FLP/FRT and fluorescent reporters to generate cell clones that provide spatial, temporal, and genetic information about the origins of individual cells in Drosophila. We name this combination the Gal4 Technique for Real-time and Clonal Expression (G-TRACE). The approach should allow for screening and the identification of real-time and lineage-traced expression patterns on a genomic scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
332
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(346 citation statements)
references
References 16 publications
(12 reference statements)
6
332
0
Order By: Relevance
“…We used a UAS-mCD8 GFP transgene to label the targeted cells and immunostaining against the cleaved form of Death Caspase 1 (Dcp1) to reveal cell death induction. Previous lineage-tracing experiments showed that col-GAL4 is expressed solely in the PSC in the primary lobes and sporadically in posterior lobes (17), whereas Antp-GAL4 is expressed in the PSC as well as in some cardiomyocytes present between the primary lobes (20) (Fig. 1 and Figs.…”
Section: Resultsmentioning
confidence: 87%
“…We used a UAS-mCD8 GFP transgene to label the targeted cells and immunostaining against the cleaved form of Death Caspase 1 (Dcp1) to reveal cell death induction. Previous lineage-tracing experiments showed that col-GAL4 is expressed solely in the PSC in the primary lobes and sporadically in posterior lobes (17), whereas Antp-GAL4 is expressed in the PSC as well as in some cardiomyocytes present between the primary lobes (20) (Fig. 1 and Figs.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, our system can also be used as a lineage-tracing tool reminiscent of the previously reported G-trace system (29). Importantly, a tubGal80ts allele can be used to repress early Gal4 activity and achieve "real-time" capture of cell-cell interactions (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Flies carrying an enhancerless GFP construct downstream of an hsp70 minimal promoter at recombinase-mediated cassette exchange (RMCE) site 53F were described pre- Evans et al 2009), carrying an FRT-flanked stop cassette between a ubiquitous promoter and a nuclear EGFP coding region on chromosome 3 ("G-TRACE cassette"), were obtained from the Bloomington Drosophila Stock Center (stock no. 32251).…”
Section: Stocks and Fly Husbandrymentioning
confidence: 99%
“…We therefore wished to provide further confirmation that these enhancers indeed activate promoters in trans. To this end, we designed a complementary system to detect transvection based on the G-TRACE tools for cell lineage analysis (Evans et al 2009). In this system, the recombinase FLP acts on a G-TRACE cassette to remove a transcriptional stop signal between a ubiquitous enhancer and a GFP transgene, resulting in robust GFP fluorescence in a cell's lineage ( Figure 3A).…”
Section: A Flp-based Assay Further Supports Transvection By Weak Clasmentioning
confidence: 99%
See 1 more Smart Citation